2017
DOI: 10.1007/s00404-017-4621-4
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroid size modifications during pregnancy and puerperium: evidence from the first systematic review of literature

Abstract: Uterine fibroids seem to be subject to a non-linear trend of modifications during pregnancy and puerperium, which may vary from myoma to myoma. Adequate evidence supports uterine fibroid systematic enlargement during the first trimester of pregnancy, while inconsistent evidence is available about the changes of uterine fibroids during second and third trimesters. In addition, the overall modifications of myomas during pregnancy and puerperium remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 31 publications
1
54
0
11
Order By: Relevance
“…Nevertheless, the modification of myomas during the second and third trimesters is not definite: probably uterine myomas let up their growth in mid pregnancy, and their size decreases during the last period of pregnancy. Also, during the pregnancy, the total modification of fibroids does not appear to be understandable [43]. During pregnancy, the surgical treatment of myomas is performed in selected cases: torsion of pedunculated fibroid, necrosis of myoma with consequent peritoneal inflammation; in fact, the risk of myomectomy and surgical complications, also during caesarean section, overcome the benefits of conservative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the modification of myomas during the second and third trimesters is not definite: probably uterine myomas let up their growth in mid pregnancy, and their size decreases during the last period of pregnancy. Also, during the pregnancy, the total modification of fibroids does not appear to be understandable [43]. During pregnancy, the surgical treatment of myomas is performed in selected cases: torsion of pedunculated fibroid, necrosis of myoma with consequent peritoneal inflammation; in fact, the risk of myomectomy and surgical complications, also during caesarean section, overcome the benefits of conservative approach.…”
Section: Discussionmentioning
confidence: 99%
“…In general, UF may grow during the first trimester, while growth during the second and third trimester is very rare in order to produce obstetrical /perinatal complications. 43,44 UF growth may be related to the chorionic gonadotropin secretion, 45 although not significantly linked to the risk of miscarriage. 13 Pregnancy and delivery complications are usually more frequent in women aged more than 30 years 46 ; as was the case in the studies we meta-analyzed.…”
Section: Discussionmentioning
confidence: 95%
“…Various studies have revealed that 60-70% of fibroids in antenatal women show no change in volume. Around 22-32% show increase in volume, especially in first trimester, with very minimal change in volume in second and third trimesters [6].…”
Section: A Rare Case Of Large Uterine Myoma In An Antenatal Women Witmentioning
confidence: 93%
“…All the investigations including complete blood count, Liver function fest, Renal function test, were sent and were within normal limits with hemoglobin 9.2 g/dl and incidence further increases with the advancing age of mother [9]. They rarely show any change in size during pregnancy but can increase in size and volume in first trimester and very rarely in second and third trimester [6] but unlike in this case the fibroid was rapidly growing in second trimester both in size and volume [6]. The exact pathogenesis of these smooth muscle tumours is not clear, but the two main ovarian steroidal hormones; oestradiol and progesterone play a significant role in its growth.…”
Section: Case Reportmentioning
confidence: 99%